RANCANG BANGUN MESIN UJI TARIK SERAT TUNGGAL BERBASIS MIKROKONTROLLER - Muhammad Arsyad Suyuti; Rusdi Nur; Ahmad Nurul Muttaqin (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Natural fibers are highly suitable for composite materials because they have high tensile strength and are environmentally friendly. One popular way to measure material strength is the tensile test, which uses an axial load force (F). This tensile test requires experimental equipment with high grip and stiffness. The focus of this research is to create a prototype digital tensile testing machine that can help the learning process in the mechanical engineering laboratory of State Polytechnic of Ujung Pandang. This digital strength test uses a strength meter that can be connected to a computer. The research method is carried out through design, which includes design, manufacture and assembly of mechanical components. Automation is carried out after this process by using electronic components to become a digital tensile testing tool. The expected result of this design is the creation of a digital tensile testing tool that has a level of accuracy in measuring the load applied to the fiber. The results of this design show that the digital tensile testing tool has the ability to measure loads up to 0.1 KN.